Tracing the provenance of inherited zircons from peraluminous granites in the Lhasa Terrane and its paleogeographic implications. - Zhu, D.C.; Zhao, Z.D.; Niu, Y.L.; Wang, Q.; Dilek, Y.; Guan, Q.; Liu, Y.S.; Mo, X.X. (科学出版社 = Science Press, 2011)
Peraluminous granites with abundant zircon inheritance are derived from partial melting of Al-rich rocks (e.g. metapelite). Thus the U-Pb age data of inherited zircons from peraluminous granites provide insights into provenance of clastic sediments in their source region, as do the detrital zircons from sedimentary rocks (and their metamorphosed equivalents). This paper reports the whole-rock geochemical and zircon U-Pb geochronological data (95 analyses) of the Early Jurassic peraluminous granites in the central Lhasa subterrane. These data, in combination with the existing data of inherited zircons (104 analyses) from the Permian and Late Triassic peraluminous granites currently available in the central Lhasa subterrane, are used to characterize the inherited zircon signature of the Lhasa Terrane. These granites belong to strongly peraluminous S-type granites, which contain abundant inherited zircons that define two main age populations of 1250~1100Ma (peak at 1181±14Ma) and 550~450Ma (peak at 494±7Ma), comparable to the ca. 1170Ma age population defined by detrital zircons from Paleozoic sedimentary rocks and the emplacement timing of Cambrian volcanic rocks in the Lhasa Terrane, respectively. The ca. 1170Ma age population defined by inherited and detrital zircons in the Lhasa Terrane differs significantly from the age distributions (peak at ca. 960Ma) defined by detrital zircons from Neoproterozoic-Paleozoic sedimentary rocks in the western Qiangtang, Amdo, and Tethyan Hiamalaya in southern Tibet. We propose that the ca. 1181Ma inherited zircons from peraluminous granites in the central Lhasa subterrane were most likely derived from the Albany-Fraser orogenic belt in southwestern Australia and Wilkes Province in East Antarctica, as do the coeval detrital zircons from Paleozoic sedimentary rocks in the Lhasa Terrane, and that the ca. 494Ma inherited zircons might have been sourced from both the Western Australia and Lhasa Terrane itself. This paper provides evidence of U-Pb dating on inherited zircons from peraluminous granites for the paleogeographic connection between the Lhasa Terrane and northern Australia. Our studies on the geology of the Lhasa Terrane indicate that a combined in-situ U-Pb dating on inherited zircons from peraluminous granites and detrital zircons from Paleozoic sedimentary rocks can provide important constraints on paleogeography and tectonomagmatic evolution of other microcontinents along the northern margin of Gondwana.